Target Tilt Gully flows into the River at the Salmon Hole - Branch Cultural Historical Association (2006)
Gully banks are good places to find various tree species. In the late 1800s, a cooper by the name of Johnny Target spent time in Branch cutting birch wood for use in barrel making. Target built a tilt near this gully and it became known as Target Tilt Gully.